2012
DOI: 10.1037/a0026651
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the effects of status and power: A justice perspective.

Abstract: Few empirical efforts have been devoted to differentiating status and power, and thus significant questions remain about differences in how status and power impact social encounters. We conducted 5 studies to address this gap. In particular, these studies tested the prediction that status and power would have opposing effects on justice enacted toward others. In the first 3 studies, we directly compared the effects of status and power on people's enactment of distributive (Study 1) and procedural (Studies 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
336
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(359 citation statements)
references
References 120 publications
(173 reference statements)
17
336
6
Order By: Relevance
“…In line with other experimental designs (20)(21)(22), our manipulation therefore included features of social status and power to emulate real-world hierarchies. The few studies to date that differentiated power and status suggest they sometimes lead to different outcomes; for instance, status often promotes, whereas power reduces, justice toward others (38). But both power and status are plausible explanations for the interactions between social rank and stability seen in the present study.…”
Section: Discussioncontrasting
confidence: 42%
“…In line with other experimental designs (20)(21)(22), our manipulation therefore included features of social status and power to emulate real-world hierarchies. The few studies to date that differentiated power and status suggest they sometimes lead to different outcomes; for instance, status often promotes, whereas power reduces, justice toward others (38). But both power and status are plausible explanations for the interactions between social rank and stability seen in the present study.…”
Section: Discussioncontrasting
confidence: 42%
“…An important difference between status and power is that, unlike status which is socially conferred, power is a property of the actor and is less susceptible to the subjective evaluations of others (Blader & Chen, 2012). We expect that this key distinction between status and power would also lead to differential effects on creativity.…”
Section: Studymentioning
confidence: 99%
“…Because power is derived from control over resources rather than conferred by the group, individuals with middle power should feel less susceptible to the threat of status loss (Blader & Chen, 2012). Hence, in Study 4, we manipulated power level (high, middle and low) and expected evaluation.…”
Section: The Present Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the majority of research has been quantitative, a variety of methods have been used to study procedural justice (Mazerolle, Bennett, Davis, Sargeant, & Manning, 2013), including: observation (Dai, Frank, & Sun, 2011;McCluskey, 2003); survey research (Ivec, V.Braithwaite, & Reinhart, 2011;Sunshine & Tyler, 2003;Tyler, Schulhofer, & Huq, 2010); and interview (Harris & Gosnell, 2012). The majority of the research has focused on the perceptions of those being regulated, the receivers of procedural justice (Blader & Chen, 2012). Very few studies have focused on those authority figures responsible for "creating justice in the first place" (Blader & Chen, 2012, p.994) and the factors that influence whether or not they enact procedurally fair processes (Blader & Chen, 2011;B.Scott, Colquitt, & Paddock, 2009 (Cherney & Murphy, 2011) and organisational (Cropanzano & Ambrose, 2001) contexts, have also identified that people may consider the opportunity for voice in decision-making processes to be tokenistic and a strategy for co-opting compliance, rather than a meaningful opportunity for input (Mazerolle et al, 2014).…”
Section: Previous Applications Of Procedural Justicementioning
confidence: 99%